Women-to-Women Diplomacy in Georgia: A Peacebuilding Strategy in Frozen Conflict. Issue 3 (3rd July 2019) - Cárdenas, Magda Lorena
ABSTRACT: This research explores strategies led by women´s grassroots organisations and discusses how they can offer opportunities for peacebuilding in frozen conflict settings such as Georgia and the breakaway territories of South Ossetia and Abkhazia. These conflicts are related to separatist aspirations which are based, on the surface, on ethnic differences. However, the precedent of inter-ethnic dialogue shows that there is not an inherent 'us-against-them' narrative separating Georgia from Abkhazia and South Ossetia. Therefore, it is possible to create alternative arenas for dialogue and mutual understanding among the parties. To this end, this study adopts a broad approach to peacebuilding as a process of social transformation of hostile attitudes and exclusive narratives. I argue that women-to-women diplomacy is a peacebuilding strategy with the potential to address the roots of polarisation by humanising the other and identifying common ground for cooperation and inter- ethnic dialogue. The empirical research based on the experiences of women's organisations in Georgia illustrates the contribution of women-to-women diplomacy to peacebuilding as an alternative platform for coalition building based on the common goal of achieving equal rights.